Heterogeneous Ferroelectric Solid Solutions Phases and Domain States - Topolov, Vitaly Yu (Springer Series in Materials Science,, 2018)
This book systematizes data on the heterophase states and their evolution in perovskite-type ferroelectric solid solutions. It also provides a general interpretation of heterophase and domain structures on changing temperature, composition or electric field, as well as the complete analysis of interconnections domain structures, unit-cell parameters changes, heterophase structures and stress relief. The description of numerous examples of heterophase states in lead-free ferroelectric solid solutions is also included. Domain state-interface diagrams put forward the interpretation of heterophase states in perovskite-type ferroelectric (FE) solid solutions and describe the stress relief in the presence of polydomain phases, the behavior of unit-cell parameters of coexisting phases, the effect of external electric field etc. This 2nd edition generalizes the results on the heterophase ferroelectric solid solutions and the stress relief and presents new results on heterophase/domain structures and phase contents in lead-free ferroelectric solid solutions. .